1968
DOI: 10.1073/pnas.60.4.1396
|View full text |Cite
|
Sign up to set email alerts
|

An early alteration in the phospholipid metabolism of lymphocytes by phytohemagglutinin.

Abstract: Phytohemagglutinin (PHA), a glycoprotein derived from the kidney bean Phaseolus vulgaris, initiates a sequential activation of RNA, protein, and DNA synthesis that leads to cell division in human lymphocytes cultured in vitro.1-3 In this response the lymphocytes present a synchronized cell system for studying the molecular steps in the transformation of a resting cell to the growing state. Definition of the interaction of PHA with the lymphocyte might thus identify key processes controlling cell replication. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1970
1970
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…The early response occurred within 1 min, sufficiently fast to suggest that cyclic AMP could play a major role in the early metabolic effects of PHA. Other early changes in lymphocyte metabolism in PHAstimulated cells include increased incorporation of 'P orthophosphate into phosphatidylinositol (20), an increased rate of phosphorylation and acetylation of nuclear protein (21), and an increased rate of incorporation of radioactive precursors into RNA and protein (22). These changes appear to occur less rapidly than the early elevation in cyclic AMP concentration.…”
Section: Resultsmentioning
confidence: 93%
“…The early response occurred within 1 min, sufficiently fast to suggest that cyclic AMP could play a major role in the early metabolic effects of PHA. Other early changes in lymphocyte metabolism in PHAstimulated cells include increased incorporation of 'P orthophosphate into phosphatidylinositol (20), an increased rate of phosphorylation and acetylation of nuclear protein (21), and an increased rate of incorporation of radioactive precursors into RNA and protein (22). These changes appear to occur less rapidly than the early elevation in cyclic AMP concentration.…”
Section: Resultsmentioning
confidence: 93%
“…Several observations suggested that the accumulation of free Ca2+ in cytosol might act as a signal for cell proliferation (18). Diacylglycerol (DG), generated by the breakdown of phosphatidylinositol 4,5-bisphosphate, was found to induce the activation of protein kinase C, and has been recognized as an important mediator for cell proliferation (3,15). Evidence has been obtained that TPA can act as a substitute for DO to activate protein kinase C (8,10), and that FGF induces DG formation, protein kinase C activation, and Ca2+ mobilization (26).…”
Section: Discussionmentioning
confidence: 99%
“…The preincubation period produced no alteration in the rate of AIB uptake either in the presence or absence of PHA indicating an absence of exchange diffusion. 2 Removal of PHA from lymphocytes. Having demonstrated that PHA can alter the membrane function of lymphocytes, we next investigated whether this effect would be sustained or reversed when the bound PHA was removed from the lymphocyte cell surface.…”
Section: Methodsmentioning
confidence: 99%
“…While numerous investigators have studied a variety of metabolic alterations which occur after lymphocytes are exposed to PHA (for a recent review see Reference 1), little attention has been focused on the effect that PHA may have on the lymphocyte plasma membrane. Recently, Fisher and Mueller (2) have reported that within minutes after PHA is added to lymphocytes there is an increase in the rate of 8P incorporation into membrane phospholipids. However, the consequences of PHA binding to lymphocytes on the functional characteristics of the plasma membrane need to be further explored.…”
Section: Introductionmentioning
confidence: 99%